Experimental investigation of solar chimney with concentrated collector (SCCC) - El Hadji I Cisse; Ababacar Thiam; Baye Alioune Ndiogou; Dorothé Azilinon; Vincent Sambou (Case Studies in Thermal Engineering, 2022)
In this article, we have experimentally studied the effect of solar radiation concentration on a solar chimney collector. We analytically measured the performance of the solar chimney with concentrated collector (SCCC) while comparing it with the performance of a solar chimney without a reflector as far as the concentration of solar radiation is concerned. The solar chimney is built on a wooden building measuring 2 m × 2 m × 2 m and located at the Higher Polytechnic School of Dakar. The purpose of this article was to evaluate the addition of reflectors (boosters) on a conventional tilted solar chimney on natural ventilation in a building. The results show that the three reflectors added to the solar chimney increased the collector solar radiation. This concentration of radiation, combined with a high absorptivity of the collector, increased the temperature of the collector. There was a noticeable temperature difference between the solar chimney with concentrated collector and the one without concentrated collector. This temperature rise has induced an elevation in velocity. Therefore, the addition of reflectors can improve the chimneys performance for a better natural ventilation in bioclimatic buildings.